2019
DOI: 10.1186/s13287-019-1434-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of BMP2 delivery by coacervate and gene therapy for promoting human muscle-derived stem cell-mediated articular cartilage repair

Abstract: BackgroundOsteoarthritis and cartilage injury treatment is an unmet clinical need. Therefore, development of new approaches to treat these diseases is critically needed. Previous work in our laboratory has shown that murine muscle-derived stem cells (MDSCs) can efficiently repair articular cartilage in an osteochondral and osteoarthritis model. However, the cartilage repair capacity of human muscle-derived stem cells has not been studied which prompt this study.MethodIn this study, we tested the in vitro chond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…SIRT1 promoted BMP-2-induced chondrogenic differentiation of MSCs and reduced the apoptosis and decomposition of the extracellular matrix under oxidative stress [ 38 ]. It has also been demonstrated that BMP-2 delivery by coacervate and gene therapy can promote human muscle-derived stem cell-mediated articular cartilage repair [ 23 ]. In fact, studies have showed that cartilage differentiation plays crucial roles in tendon and bone interface healing [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 promoted BMP-2-induced chondrogenic differentiation of MSCs and reduced the apoptosis and decomposition of the extracellular matrix under oxidative stress [ 38 ]. It has also been demonstrated that BMP-2 delivery by coacervate and gene therapy can promote human muscle-derived stem cell-mediated articular cartilage repair [ 23 ]. In fact, studies have showed that cartilage differentiation plays crucial roles in tendon and bone interface healing [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the strategies toward improving the outcome of exogenous or endogenous reparative cell-based cartilage repair is to optimize the local milieu for such cells to properly rebuild the articular cartilaginous tissue in the damaged site, using factors that are known to directly or indirectly enhance chondrogenesis from MSCs and SSCs in vitro and in vivo. Such factors include transforming growth factor beta (TGF-β) [ 25 , 26 , 27 ], bone morphogenetic protein (BMP) [ 28 , 29 , 30 , 31 ], fibroblast growth factor 18 (FGF18) [ 32 , 33 ], insulin-like growth factor 1 (IGF1) [ 34 , 35 ], and stromal cell-derived factor 1 (SDF1/CXCL12) [ 36 , 37 ]. These factors have been preclinically and clinically tested and resulted in some positive outcomes [ 8 ].…”
Section: Biologics For Improving Local Milieu For Endogenous and Exogenous Chondrogenic Cells To Properly Repair Articular Cartilage Damamentioning
confidence: 99%
“…Among the chondrogenic growth factors, bone morphogenetic protein (BMP)-4, BMP-6, BMP-7, transforming growth factor (TGF)-βs, insulin-like growth factor (IGF)-1 and BMP-2 have been demonstrated to be the most effective [ 12 , 13 , 14 ]. BMP-2 is a member of the TGF-β superfamily and a potent regulator of cartilage growth and development [ 5 , 15 , 16 ]. BMP-2 has also been applied as a chondroinductive factor to promote MSC chondrogenesis [ 12 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…BMP-2 is a member of the TGF-β superfamily and a potent regulator of cartilage growth and development [ 5 , 15 , 16 ]. BMP-2 has also been applied as a chondroinductive factor to promote MSC chondrogenesis [ 12 , 15 , 16 , 17 , 18 ]. However, BMP-2 also exerts osteogenic effects on MSCs [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%